Determinants of accounting fraud in Paser regency regional apparatus - Nor, Wahyudin; Purnamasari, Wulan; Lesmanawati, Dewi (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
Accounting fraud can occur in the private and government sectors. This study aims to test and analyze the factors that affect accounting fraud in the Paser Regency Regional Apparatus. The population consists of 218, with a sample of 87 respondents consisting of the Head of the agency/agency, Secretary, Head of Finance, and officials involved in using funds and preparing financial statements. Data were collected through questionnaires measured using the Likert scale and analyzed by regression analysis using SPSS 25. Based on the results of the analysis, it was found that the variable perception of compensation suitability negatively affects accounting fraud. While information asymmetry, internal control, individual morality, observance of accounting rules, and internal audit do not affect accounting fraud. The Paser Regency government should close the opportunity for fraud by tightening financial management and reporting supervision, paying attention to and maintaining compensation adjustments, including incentives and other benefits to minimize fraud.